Jeremia en die woord in ’n tyd van krisis - Van Rooy, H. F. (Koers, 1988)
Jeremiah and his work and book have a message for everyone who has to preach the Word of God. He was called to proclaim a message of doom in a time of national crisis. Often he had to oppose the leaders of his people and the people themselves. This paper gives attention to some problems regarding the prophet and his relation to the book of Jeremiah, the times of Jeremiah, the Word in a time of theological and political crisis, the crisis in the life and work of the prophet and the Book of Jeremiah in the context of the crisis of the exile and thereafter. The importance is demonstrated of taking at least a dual address into consideration when studying the Book of Jeremiah, namely the people of the time of Jeremiah and the people of the Babylonian exile.